PERSPEKTIF PEMILIK USAHA RUMAH KOS TENRANG PEMAHAMAN PAJAK HOTEL TERKAIT PENINGKATAN PENDAPATAN ASLI DAERAH KOTA MAKASSAR - Andi Rustam; Ismail Rasulong; Indri Nursyafirah (Jurnal Riset Perpajakan: Amnesty, 2021)
The purpose of this study is to determine the perspective of boarding house business owners regarding their understanding of the boarding house category hotel tax in Makassar City. This type of research is a qualitative descriptive study. Data collection techniques using literature study, observation, interviews and documentation. Data analysis techniques used data reduction, data presentation, and drawing conclusions. The results of this study indicate that the perspective of boarding house business owners regarding the hotel tax in the boarding house category is still lacking due to the lack of socialization from the government and the hotel tax rate for the boarding house category is still considered burdensome, causing tax avoidance.